(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The aim of this paper is to examine and evaluate the effectiveness of ABL method compared with the existing or traditional methods of English language teaching in higher secondary schools in Kerala and to substantiate that ABL method brings a revolutionary attitudinal modification in the level of perception in students than any other methods of learning and acquiring language proficiency. The study continues to establish that the ABL method results in more students’ activities and lesser teacher domination in the class room and there by the monopoly of teacher is totally wiped out and the students are empowered.